A avaliação do curriculo integrado no PROEJA do IFCE: concepção e prática na percepção do docente - Araújo, Ana Cláudia Uchôa (2010)
This research was motivated by the initial need of a curriculum evaluation to understand how the curriculum of PROEJA (National Program for Integration of Basic Education with Professional Education for Youth and Adults) has been developed at IFCE (Federal Institute of Education, Science and Technology of Ceará) in the Campus of Fortaleza. It was developed under the Course Assessment axis, which is part of the Educational Evaluation line of research, and its general point is to understand the nature of the course curriculum of High School Courses integrated with the Telecommunications and Heating & refrigeration Technical Courses offered by IFCE to Youth and adults, analyzing their design and dynamic according to the teachers and identifying elements of that avaliation. The research objectives were to investigate the nature of the curriculum at prescriptive (documentary) and perceptual (vision of teachers) levels in order to analyze the perceptions of teachers and administrators on the curriculum of the courses mentioned above; and to investigate how the coordination of the courses guides the implementation of the existing curriculum taking in account the need to connect the workup training to the technical training and provides the necessary conditions to propose an ongoing curriculum evaluation. We adopted a qualitative methodology in a phenomenological approach, in which documents review and semi-structured interviews with a reflective proposal were used. The theoretical framework was supported by Silva (2007), Freire (1987), Frigotto et. al. (2005) and Vianna (2000), among other theorists who study Youth and Adult Education, the curriculum evaluation and curriculum issues. The findings of the research showed, among other data, that IFCE needs to prioritize PROEJA’s recognition. In order to achieve this goal, the implementation of structural actions, whose aim is the strengthening of PROEJA, as well as its consolidation as an institutional policy for Professional Education at this very institution are required. Therefore, special attention should be given to the active teacher training program and to the course curriculum, so that the training meets the peculiarities of Youth and Adults Education, high school and vocational training, without disregarding the interests of their students.